1642. Safety and Efficacy of Bacteriophage Therapy: Analysis of Clinical Case Series Data. (26th November 2018) - Aslam, Saima; Gilbey, Timothy; Maddocks, Susan; Morales, Sandra; Lehman, Susan; Branston, Steven; Fabijan, Aleksandra Petrovic; Furr, Carrie-Lynn Langlais; Rosas, Francisco; Bilinsky, Igor; Grint, Paul; Schooley, Robert T; et al.
Abstract: Background: Bacteriophage therapy (BT) is a re-emerging strategy to treat antibiotic-resistant infections. Here, we describe our initial experience with intravenous (IV) and inhaled BT to treat life-threatening Staphylococcus aureus and Pseudomonas aeruginosa infections not responding to antibiotic therapy. Emergency Investigational New Drug application approvals (United States) or Special Access Scheme Category A notifications (Australia) and informed consent from the patients were obtained. Methods: Patients were treated with AB-SA01 (3-phage product targeting S. aureus ) and AB-PA01 (4-phage product targeting P. aeruginosa ) produced in a Good Manufacturing Practice-certified facility. Pre- and posttreatment bacterial isolates were tested for phage susceptibility during BT. In all cases, concomitant antibiotics were continued. Safety was assessed clinically and using laboratory parameters with up to 90 days of follow-up. Samples to assess bacterial loads, bacteriophage kinetics in blood, and immune responses to phage were collected. Results: As of April 2018, 8 patients were treated with BT; 5 with AB-SA01 (bacteremia, n = 4; endocarditis, n = 1) and 3 with AB-PA01 (lung infection, n = 3). Median duration of BT was 14 days and treated patients received over 90 IV doses of AB-SA01 (3 × 10 9 PFU/dose) and over 490 IV and nebulized doses of AB-PA01 (4 × 10 9 PFU/dose). BT was well tolerated, with no treatment-related adverse events. Clinical treatment success was documented in 75% of patients. Isolates collected during therapy showed ongoing susceptibility to the BT products with changes in sensitivity to the individual phage components observed in some cases. Bacteriophage kinetics revealed bloodstream clearance within a few hours after IV infusion, with an inferred initial bacteria:bacteriophage ratio of ~200 for the bacteremia patients. Conclusion: BT was well tolerated as an adjunct to antibiotics, with several examples presented of microbiological eradication and improvement of objective clinical criteria. BT appears to be a safe adjunct to antibiotic therapy in life-threatening S. aureus and P. aeruginosa infections and is a promising candidate for controlled clinical trials. Disclosures: S. Morales, AmpliPhi Biosciences: Employee, Salary. S. Lehman, AmpliPhi Biosciences: Employee, Salary. S. Branston, AmpliPhi Biosciences: Employee, Salary. A. Petrovic Fabijan, AmpliPhi Biosciences: Collaborator, Research support. C. L. Langlais Furr, AmpliPhi Biosciences: Employee, Salary. F. Rosas, AmpliPhi Biosciences: Employee, Salary. I. Bilinsky, AmpliPhi Biosciences: Employee and Shareholder, Salary. P. Grint, AmpliPhi Biosciences: Board Member, Employee and Shareholder, Salary. J. Iredell, AmpliPhi Biosciences: Collaborator, Research support.